Presupuesto público. Motor de desarrollo y transformación social (2018)
Within what the public budget means in the current context, it is mandatory, inorder to understand its theoretical and practical sense, to comprehensively understand everything related to fiscal policy, which explains not only the meaning of taxes (fees) as an exercise that they must lead the different governments, but also reveals because in the administrations it is necessary to think of adequate public spending, which allows, therefore, to generate scenarios of development and social transformation in their environment.Thus, this article aims to approach the concept of public budget, not only to understand its epistemological basis, but to achieve evidence of the anchoring between it and the interests of the administrations, which allow, among other things, to see the budget public double-track, as an income that translates into spending, for the greatest social benefit. In conclusion, the following lines have been thought to understand why the budget, is that tool that contributes to the fulfilment of the objectives that are projected from the administrations in order to do a true social transformation.